2021
DOI: 10.1186/s13072-021-00392-w
|View full text |Cite
|
Sign up to set email alerts
|

Early-life undernutrition induces enhancer RNA remodeling in mice liver

Abstract: Background Maternal protein restriction diet (PRD) increases the risk of metabolic dysfunction in adulthood, the mechanisms during the early life of offspring are still poorly understood. Apart from genetic factors, epigenetic mechanisms are crucial to offer phenotypic plasticity in response to environmental situations and transmission. Enhancer-associated noncoding RNAs (eRNAs) transcription serves as a robust indicator of enhancer activation, and have potential roles in mediating enhancer fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Notably, expression patterns of these RNAs are known to be tissue specific, which makes them attractive as potential therapeutic targets 114 . Expression of eRNAs is also stimulus specific; for instance, particular subsets of eRNAs are preferentially expressed at inflammation-related genes in response to inflammatory stimuli, in neurons during the stimulus-induced expression of immediate early genes and after exposure to early-life undernutrition 115 117 . An experience-induced enhancer lncRNA, ADRAM (activity-dependent lncRNA associated with memory), is generated by an enhancer of Nr4a2 (nuclear receptor subfamily 4, group A, member 2).…”
Section: Nbts For Protein Upregulationmentioning
confidence: 99%
“…Notably, expression patterns of these RNAs are known to be tissue specific, which makes them attractive as potential therapeutic targets 114 . Expression of eRNAs is also stimulus specific; for instance, particular subsets of eRNAs are preferentially expressed at inflammation-related genes in response to inflammatory stimuli, in neurons during the stimulus-induced expression of immediate early genes and after exposure to early-life undernutrition 115 117 . An experience-induced enhancer lncRNA, ADRAM (activity-dependent lncRNA associated with memory), is generated by an enhancer of Nr4a2 (nuclear receptor subfamily 4, group A, member 2).…”
Section: Nbts For Protein Upregulationmentioning
confidence: 99%
“…For instance, eRNAs are preferentially expressed at inflammation-related genes in response to inflammatory stimuli (Wan et al, 2022). Global run-on sequencing (GRO-seq) has demonstrated that expression of eRNA is altered in response to early-life undernutrition (Wang Y. et al, 2021). In neurons, eRNAs are expressed at immediate early genes after stimulus.…”
Section: Regulation Of Erna Expressionmentioning
confidence: 99%